انتہا پسندی: خاندانی نظام کی کمزوریوں اور سماجی بگاڑ کا تجزیاتی جائزہ: Extremism: An Analytical Study of Family System Vulnerabilities and Social Disintegration DOI: https://doi.org/10.5281/zenodo.17694236 (Khairulummah, 2024)
This study critically analyzes the impact of extremism on the stability of family structures and the broader social fabric. It explores how extremist ideologies infiltrate domestic life, weakening familial bonds, disrupting communication, and fostering an environment of fear, intolerance, and psychological stress. The research further examines the social consequences of such ideologies, including polarization, breakdown of community cohesion, erosion of mutual trust, and the rise of violence and discrimination. Drawing on contemporary scholarship and Islamic teachings, the study highlights the underlying causes that allow extremism to penetrate social systems and proposes comprehensive strategies—educational, ethical, and community-based—to counter its influence. The findings underscore the urgent need for balanced intellectual frameworks and strong moral values to safeguard families and societies from the destructive effects of extremism.
Keywords: Extremism; Family Structure; Social Disintegration; Domestic Stability; Community Cohesion; Islamic Teachings; Social Harmony; Violence; Psychological Impact.